General aspects of 3D printing applied to civil construction: a review - Dias, Leonardo de Souza (2024)
Additive manufacturing, also called 3D printing, has been gaining ground in different sectors of industry, the arts, in addition to the biomedical environment. In recent years, this has been incorporated as a research and practice niche in civil engineering. The execution of works, at the stage where the inclusion of this technology stands, is crucial in understanding the variants and challenges of the process. In this sense, the present study aims to raise and discuss issues involving the 3D printing of cementitious compounds, bringing aspects of the printing system and the materials of the mixtures used, and observing the effects that these can cause on the quality and the final performance of the structure built. It is a review of the literature developed based on the search in the scientific databases ScienceDirect, Scopus, and Francis & Taylor, using selected descriptors, which resulted, after applying the inclusion and exclusion criteria, in a total of 295 findings. Among other characteristics, it was possible to perceive the predominance of the extrusion-based procedure, in addition to how the components of the different execution approaches, as well as constituents of the mixture, modify the characteristics of the product in its fresh and hardened state. In general, additive manufacturing proves to be suitable for use, making the improvements and discoveries brought by researchers an impulse for the technique to be a possible advance in the automation of the sector.